OPTIMALISASI SEARCH ENGINE & SOCIAL MEDIA MARKETING : STRATEGI MENINGKATKAN MINAT WISATAWAN DI KABUPATEN BANDUNG BARAT (KBB): Search Engine Optimization, Social Media Marketing, Brand Knowledge, Travel Interest, West Bandung Regency Tourism - Dinda Kayani Putri Bestari; Gina Apryani Nurunnisha (Jurnal Ilmu Manajemen (JIMMU), 2023)
Indonesia has incredible natural beauty, cultural diversity, and interesting historical values. West Bandung Regency (KBB), is one of the places where tourism is growing rapidly. This is indicated by the number of tourist destinations spread across two divisions (12) sub-districts in the West Bandung Regency (KBB) area, currently the total number of tourist destinations in the KBB area is forty-one destinations. However, based on data from the West Java Regional Opinion Agency, in 2021 there was a decrease in the number of tourists by 44%, this cannot be ignored considering the large potential for regional income from natural tourism in the KBB region. Through this research, the author aims to analyze the utilization of search engine optimization, social media marketing as an effort to increase tourist interest in the West Bandung Regency (KBB) area which ultimately has an impact on customer live value for the tourism sector. The respondents in this study were 150 people who live in Bandung and Jabodetabek. The results of this study indicate that there is a significant influence of the application of SMM and SEO on the formation of brand knowledge and indirectly has an impact on interest in traveling to Sarae Hills tourist area, West Bandung Regency, precisely has a significant impact on preferential and exploratory interest. However, the interactivity indicator in the SMM variable has a fairly low influence, this is because the information conveyed through Sarae Hills social media content is considered informative enough. Furthermore, in the SEO variable, organic search engine optimization is still a solution, considering the impact of organic search optimization has a long-term impact on the formation of company value.